2004
DOI: 10.1126/science.1092138
|View full text |Cite
|
Sign up to set email alerts
|

PEST Domain-Enriched Tyrosine Phosphatase (PEP) Regulation of Effector/Memory T Cells

Abstract: Protein tyrosine kinases and phosphatases cooperate to regulate normal immune cell function. We examined the role of PEST domain-enriched tyrosine phosphatase (PEP) in regulating T cell antigen-receptor function during thymocyte development and peripheral T cell differentiation. Although normal naïve T cell functions were retained in pep-deficient mice, effector/memory T cells demonstrated enhanced activation of Lck. In turn, this resulted in increased expansion and function of the effector/memory T cell pool,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
420
1
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(465 citation statements)
references
References 24 publications
41
420
1
3
Order By: Relevance
“…Knockout mice deficient for PTPN22 show selective dysregulation in the effector/memory T-cell compartment, with hyperproliferation and early signalling responses in restimulated T cells, compared with essentially normal responses in naïve T lymphocytes. 29 High-level spontaneous germinal centre formation and elevated titres of T-cell-dependent antibodies immunoglobulin (Ig) G1 and IgG2 are also demonstrated in PTPN22 knockouts. 29 Furthermore, RNAi experiments have demonstrated that reduced LYP expression in Jurkat's cells occurs concomitantly with an increase in the expression of T-cell receptordependent activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockout mice deficient for PTPN22 show selective dysregulation in the effector/memory T-cell compartment, with hyperproliferation and early signalling responses in restimulated T cells, compared with essentially normal responses in naïve T lymphocytes. 29 High-level spontaneous germinal centre formation and elevated titres of T-cell-dependent antibodies immunoglobulin (Ig) G1 and IgG2 are also demonstrated in PTPN22 knockouts. 29 Furthermore, RNAi experiments have demonstrated that reduced LYP expression in Jurkat's cells occurs concomitantly with an increase in the expression of T-cell receptordependent activation.…”
Section: Discussionmentioning
confidence: 99%
“…29 High-level spontaneous germinal centre formation and elevated titres of T-cell-dependent antibodies immunoglobulin (Ig) G1 and IgG2 are also demonstrated in PTPN22 knockouts. 29 Furthermore, RNAi experiments have demonstrated that reduced LYP expression in Jurkat's cells occurs concomitantly with an increase in the expression of T-cell receptordependent activation. 25 The downregulatory activity of LYP is mediated as a complex with CSK, which suppresses the T-cell receptor signalling kinases LCK and FYN.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have shown that the PTPN22 T alleleencoded protein binds less efficiently to Csk, suggesting that the T cells expressing the T allele are hyperresponsive (30). Knocking out the murine homolog of PTPN22 resulted in lower thresholds of T cell activation and induced an increased expansion and function of the effector/memory T cell pool, which was associated with elevated levels of serum antibodies (35).…”
Section: Risk Factors For Acpa-positive Ramentioning
confidence: 99%
“…Thus, early experiments showed that generalized phosphatase inhibition results in persistent proliferation of polyclonally activated T cells (15) or can induce spontaneous activation and cytokine release by resting T cells (16). A specific role of PTPN22 in T cell regulation has been confirmed by the results of knocking out the murine homolog of PTPN22 (PEST domainenriched tyrosine phosphatase [PEP]), resulting in lowered thresholds for T cell receptor signaling in these animals (17). PEP-knockout mice on a nonautoimmune background (C57BL6) exhibit a variety of phenotypes consistent with T cell hyperresponsiveness, including enlargement of the spleen and lymph nodes due to T cell proliferation.…”
Section: Peter K Gregersen and Franak Batliwallamentioning
confidence: 99%